2018
DOI: 10.13189/app.2018.060202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin Supplement on Some Bone Mineralization Biomarkers in Diabetic Type 2 Patients

Abstract: Background: Diabetes associated with multiple metabolic problems in the body, including bone mineralization remodeling, osteoporosis and increase risk of fracture. Quercetin is natural flavonoids and according to animal studies; it has potent antioxidant, antidiabetic and protective effect against bone loss due to various causes. Objectives: explore effect of quercetin as nutritional supplement administrated orally on some bone mineralization bio-markers such as calcium, vitamin D and osteocalcin in Iraqi diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Based on its actions on bone, an interventional double-blind placebo randomised controlled study investigated the effects of quercetin supplementation on bone mineralisation biomarkers in patients with type 2 diabetes mellitus. In this study, patients receiving quercetin oral supplement at 500 mg/day for three months had higher levels of serum osteocalcin, calcium and vitamin D compared to their pretreatment values [ 28 ]. However, the direct effects of quercetin on bone in osteoporotic patients are still unconfirmed.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its actions on bone, an interventional double-blind placebo randomised controlled study investigated the effects of quercetin supplementation on bone mineralisation biomarkers in patients with type 2 diabetes mellitus. In this study, patients receiving quercetin oral supplement at 500 mg/day for three months had higher levels of serum osteocalcin, calcium and vitamin D compared to their pretreatment values [ 28 ]. However, the direct effects of quercetin on bone in osteoporotic patients are still unconfirmed.…”
Section: Perspectivesmentioning
confidence: 99%
“…Quercetin is a natural dietary bioflavonoid present ubiquitously in fruits and vegetables. The reported beneficial effects of quercetin include cardioprotective [ 15 ], neuroprotective [ 16 ], gastroprotective [ 17 ], anticarcinogenic [ 18 ], antimicrobial [ 19 ], anti-atherosclerotic [ 20 ], anti-inflammatory [ 21 , 22 ], antioxidative [ 21 , 23 ], immunomodulatory [ 22 ], antihypertensive [ 24 ], anti-obesity [ 25 ], antihyperglycaemic [ 26 ], lipid-modulating [ 27 ] and bone-conserving properties [ 28 ]. Amongst these, several bioactivities of quercetin make it a potential agent for maintaining bone health.…”
Section: Introductionmentioning
confidence: 99%
“…19 Despite the importance of melatonin in these biological functions, its role in diminishing osteoporosis in women in perimenopause is not fully understood. 20 In this research, melatonin is an oral supplement used for 2 months for women in perimenopause to study its effect on biochemical markers related to bones mineralization for study group, and compared to placebo, this method is similar to method done by Falah et al and Jubran et al 21,22 Melatonin administration was able to provide a rapid increase in the serum concentration of bone markers: osteocalcin, vitamin D, calcium, and CTX-1 significantly (p < 0.05) compared to control group. This is the principal endpoint in our research, and these results were different from results of many studies that found the use of melatonin has no effect on the level of osteocalcin and other measured markers.…”
Section: Discussionmentioning
confidence: 99%
“…Welch et al (2012) concluded that habitual flavonoid intake was positively associated with bone mineral density in both the hip and spine regions. Hassan et al (2018) found a strong association between an increase in the osteocalcin and elevation in serum calcium after administration of quercetin. This may indicate modulation of bone mineralization (Ducy et al, 1996).…”
Section: Putative Effects Of Nutritive Polyphenols On Bone Metabolismmentioning
confidence: 89%
“…a major class of phytochemicals found ubiquitously in fruit and vegetables (Hardcastle et al, 2011). Hassan et al (2018) and Marwan and Saleh (2012) showed a significant correlation between the use of selected polyphenols and elevation of serum calcium, vitamin D, and osteocalcin levels as markers of modulation in bone mineralization. Based on the results of a cohort study, Hardcastle et al (2011) found a significant association between flavonoid intake and bone mineral density in the hip and lumbar spine and a negative correlation with bone-resorption markers.…”
Section: Putative Effects Of Nutritive Polyphenols On Bone Metabolismmentioning
confidence: 99%